Folklore Utilisation of Bryophtes amongst the Tribal Regions of North Coastal Andhra - Rao, G. M. Narasimha; Chatterjee, Reshmi (International Journal of Environment, 2014)
Bryophyte which is otherwise considered to be as Lilliputians amongst the land plants is found to be highly priced for the preparation of ethnomedicines. Ethnic tribes depend upon the plant in their surroundings for traditional medicine preparation. The present article enumerates four species of bryophyte which are used routinely amongst the tribes of North coastal Andhra to treat various ailments. Bryophytes are ecologically friable and very prone to extinction. Hence, these types of studies are important as it will bring more and more new species of bryophyte with exceptional therapeutic properties into light.DOI: http://dx.doi.org/10.3126/ije.v3i4.11734       International Journal of Environment Volume-3, Issue-4, Sep-Nov 2014Page: 101-108